Liver Diseases in the Perinatal Period: Interactions Between Mother and Infant. Issue 4 (18th March 2020) - Ibrahim, Samar H.; Jonas, Maureen M.; Taylor, Sarah A.; Gutierrez Sanchez, Luz Helena; Wolf, Jaqueline L.; Sundaram, Shikha S.
Abstract : Liver diseases affecting the mother and infant dyad may present in the perinatal period from 20 weeks of gestation to 28 days of life. This review will focus on the current approach to neonatal acute liver failure and the progress made in the diagnosis and management of gestational alloimmune liver disease. It will highlight mother‐to‐child transmission of viral hepatitis, both management and public health implications. Emerging concepts implicating maternal obesity and nutrition in the development of a rapidly progressive nonalcoholic steatohepatitis phenotype in the offspring will be discussed. Finally, the presentation and management of acute fatty liver of pregnancy and intrahepatic cholestasis of pregnancy, and their impact on the fetus, will be reviewed.